PENGARUH MOTIVASI BERPRESTASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MARKETING FUNDING DI BANK MUAMALAT SURABAYA - Maslihatiddiniyah, Vidiya; Rachmawati, Lucky (Universitas Negeri Surabaya, 2020)
This research is aimed to see the impact of achievement motivation and compensation toward the performance of funding marketing employees in Muamalat Bank Surabaya Branch. This study uses a saturated sample by involving the intire population to be sampled. In thi study there were 30 employee of funding marketing in Muamalat Bank Surabaya Branch from 3 different branches namely The Main Branch Office-Mas Mansyur, The Main Branch Office-Darmo, and The Main Branch Office-Mayjend Sungkono. The data collection technique applied in this research is a questionnaire with a list of questions addressed to the respondent using a Likert scale in the checklist-shaped with 5 options answer. The test measuring instruments such as multiple linear regression and hypothesis test consists of t-test, f-test, and determination coefficient (R2) are employed as the data analysis technique. The finding resulted that, simultaneously, the variable of achievement motivation and compensation is positively influenced the performance of funding marketing employees in Muamalat Bank Surabaya Branch. Meanwhile, partially, it resulted that achievement motivation and compensation are significantly and positively impacted the performance of the employees. While the results of the coefficient of determination (R2) test gives an effect of 46.2% on the performance of marketing funding employees at Muamalat Bank Surabaya. While the remaining 53.8% of the variables are put outside the research.